Molecular and Phylogenetic Detection of Torque Teno Virus (TTV) Among Hemodialysis Patients: A Single Center Study (Iraqi Journal of Medical Sciences, 2022)
Background: Patients on long-term hemodialysis are at a higher risk of contracting blood transmitted infections because of their weakened immune systems and frequent interaction with blood, blood products, equipment, and contaminated surfaces. This making them an important population to study the clinical and epidemiological consequences of newly discovered infections like torque teno virus (TTV).Objective: To investigate the frequency of TTV in patients undergoing hemodialysis by molecular method and to find out any association with risk factors and liver function tests.Methods: This cross-sectional study conducted on (100) patients whom attending Hemodialysis Unit at Al-Imamein Al-Kadhimein Medical City in Baghdad, Iraq. The sample of the study consist of (58) males and (42) females, their mean age is (49.97±4.97 SD) years, (50) with viral hepatitis, while (50) without viral hepatitis, for a period from November 2020 to March 2021. Nested polymerase chain reaction (PCR) was used to detect TTV-DNA. TTV genogroup was determined by Sanger sequencing and phylogenetic tree construction.Results: TTV DNA was detected in 81% (81 out of 100) of hemodialysis patients, respectively. However, no significant association was found between demographic data, clinical characteristics and risk factors with TTV infection.Conclusion: This study showed high prevalence of TTV in hemodialysis patients but didn't play a role in liver injury among these patients. Also, based on phylogenetic analysis of the untranslated region (UTR), genogroup-3 was found to be the most prevalent in hemodialysis patients.Keywords: Torque teno virus, hemodialysis, risk factors, liver function, sequencing, phylogenetic treeCitation: Ali HM, Al-Shuwaikh AM, Manuti K. Molecular and phylogenetic detection of Torque Teno Virus (TTV) among hemodialysis patients: A single center study. Iraqi JMS. 2022; 20(1): 11-25. doi: 10.22578/IJMS.20.1.3
Keywords: Torque teno virus; hemodialysis; risk factors; liver function; sequencing; phylogenetic tree